Sosialisasi Dan Pembagian Masker Gratis Masa Pandemi Sebagai Upaya Preventif Covid-19 - Halisa Suriani; Muhammad Yassir; Orbit Irwansyah; Afrizal Afrizal; Isnaini Isnaini (JURNAL PRODIKMAS Hasil Pengabdian Kepada Masyarakat, 2020)
The implementation of this activity was carried out on Monday 9 November 2020 by Lecturers and students and assisted by the local community, starting with program discussions and taking a door approach. Before starting the socialization program,the licensing process was carried out in accordance with health protocols while simultaneously providing socialization about Cvid-19 in every house near the UGL Kutacane campus which was carried out door to door and distributing free masks to the public as a Covid-19 preventive effort. Socialization activities and distribution of masks to he community received positive appreciation from the community because the socialization was also carried out door to door by taking a direct approach to the community and this was very much needed in the midst of the Covid-19 pandemic.